Quantifying Ocean-Atmosphere-Ecosystem Coupling: Precipitation-Chlorophyll Lag Relationship in West Java Using Decade-Long Satellite Observations - Muhammad Fatan Rzaqa; Satria Sandi Pratama; Carolina Angel; Nailil Izzah; Haura Azalia Putri Fardian; Jogi Panggabean (Sean Institute, 2026)
Understanding predictive relationships between oceanic conditions and extreme rainfall is crucial for improving weather forecasting capabilities in tropical maritime regions. This study investigates quantitative relationships between precipitation, chlorophyll-a concentrations, and extreme rainfall patterns in West Java using 10 years of satellite observations (2014-2024). We analyzed IMERG precipitation data and MODIS chlorophyll-a products using cross-correlation analysis, continuous wavelet transform, cross-wavelet coherence, and spatial extreme indices calculations. Results reveal statistically significant coupling between precipitation and chlorophyll-a (r = -0.173, p < 0.001) with precipitation leading chlorophyll decrease by 19 days, reflecting marine ecosystem responses to terrestrial runoff. Cross-wavelet coherence analysis demonstrates 78% annual coherence and 68% semi-annual coherence between these variables, with 72.5% of total variance explained by significant periodic interactions. Wavelet analysis identifies dominant annual and semi-annual cycles in both precipitation and chlorophyll-a with 95% statistical significance. Spatial analysis using k-means clustering reveals four distinct precipitation regimes: northern coastal zones with prolonged dry periods (>45 days), central highlands with intense convective activity (>3000 mm annually), southern mountains with extreme precipitation (>3200 mm), and transitional zones with mixed characteristics. Spatial autocorrelation analysis confirms significant clustering (Moran's I = 0.65-0.89) of precipitation extremes across the region. The identified 19-day lead-lag relationship provides a scientific foundation for marine ecosystem monitoring and represents a significant advancement in understanding ocean-atmosphere-ecosystem coupling processes in tropical Indonesia. These findings have important implications for developing improved seasonal forecasting capabilities and ecosystem-based climate adaptation strategies. Keywords: Climate variability; Extreme precipitation; Lead-lag correlation; Tropical meteorology; Wavelet analysis; Cross-wavelet coherence; Marine ecosystems